Leaf extracts of Melia azedarach Linnaeus (Sapindales: Meliaceae) act as larvicide against Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae) - Prophiro,Josiane Somariva (2008)
The objective of this study was to compare the larvicidal effect of hydroethanolic extracts of fresh and dry leaves of Melia azedarach Linnaeus (Sapindales: Meliaceae) on Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae). All the extracts evaluated induced mortality among the third and fourth instar larvae of Aedes aegypti after 24 and 48 hours of exposure to the products. Although previous studies had demonstrated the action of seeds and fruits of Melia azedarach against the larvae of different Aedes aegypti populations, the present report is the first to show the larvicidal effect of the fresh and dry leaves of this plant.